2018
DOI: 10.1038/s41594-018-0023-y
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structures of PRC2 simultaneously engaged with two functionally distinct nucleosomes

Abstract: Epigenetic regulation is mediated by protein complexes that couple recognition of chromatin marks to activity or recruitment of chromatin-modifying enzymes. Polycomb repressive complex 2 (PRC2), a gene silencer that methylates lysine 27 of histone H3, is stimulated upon recognition of its own catalytic product, and has been shown to be more active on dinucleosomes than H3 tails or single nucleosomes. These properties likely facilitate local H3K27me2/3 spreading causing heterochromatin formation and gene repres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
268
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(282 citation statements)
references
References 54 publications
14
268
0
Order By: Relevance
“…Accordingly, we first produced a full-length model of the wild-type GluN1-GluN2B NMDAR (lacking the C-terminus) combining the information of the inhibited state crystal structures (in complex with agonists and a GluN2B allosteric inhibitor; Lee et al, 2014) and reconstructing the missing loops (see Material and Methods). We then modeled the transitions between the different structures of the receptor using iMODfit (Lopez-Blanco & Chacon, 2013 and see Material and Methods), a program allowing flexible fitting of atomic structures into EM maps based on Normal Mode Analysis, and that has proven useful to study concerted motions of biomolecular structures (e.g., Gatsogiannis et al, 2016;Newcombe et al, 2018;Poepsel et al, 2018). When fitting our full-length model of the inhibited state into the TMD-missing "active" state EM map, several features caught our attention (Fig 4, Movies EV1 and EV2).…”
Section: Super-active Receptors Are Resistant To Ntd-mediated Allostementioning
confidence: 99%
“…Accordingly, we first produced a full-length model of the wild-type GluN1-GluN2B NMDAR (lacking the C-terminus) combining the information of the inhibited state crystal structures (in complex with agonists and a GluN2B allosteric inhibitor; Lee et al, 2014) and reconstructing the missing loops (see Material and Methods). We then modeled the transitions between the different structures of the receptor using iMODfit (Lopez-Blanco & Chacon, 2013 and see Material and Methods), a program allowing flexible fitting of atomic structures into EM maps based on Normal Mode Analysis, and that has proven useful to study concerted motions of biomolecular structures (e.g., Gatsogiannis et al, 2016;Newcombe et al, 2018;Poepsel et al, 2018). When fitting our full-length model of the inhibited state into the TMD-missing "active" state EM map, several features caught our attention (Fig 4, Movies EV1 and EV2).…”
Section: Super-active Receptors Are Resistant To Ntd-mediated Allostementioning
confidence: 99%
“…The PRC2 structure, with four core subunits, SUZ12, EZH2, EED, and RBBP4, was constructed using homology modeling (19). Close examination of the docking results revealed that, consistent with the published cryo-EM structure (6), PRC2 can interact with adjacent nucleosomes using EED and EZH2 subunits (Nucl1-2 mode). Repeating the docking procedure using the same system as in the cryo-EM study with a dinucleosome structure led to similar conclusions ( Figure S6).…”
Section: In Silico Characterization Of Prc2-chromatin Interactionsmentioning
confidence: 57%
“…Missing residues that cannot be found in any of the PDB structures were built as random loops. An initial configuration for the tetranucleosome was obtained by sequentially extending the dinucleosome cryo-EM structure (6). A 30-bp-long linker DNA (sequence: TATGACAGTGCATCACGGGGTGAGATCGCT) was used to connect the 2 nd /3 rd and the 3 rd /4 th nucleosomes.…”
Section: Computer Modeling and Simulationsmentioning
confidence: 99%
“…This interaction was visualized by ac ryo-EMs tructure reported by the group of Nogales. [10] One of the pair of nucleosomesi sa nu nmodified substrate,a nd the other one has histone H3K27me3 marks. PRC2 interactsw ith nucleosomes, not on the acidic patch of the histone H2A/H2Bs urface, but through DNA interactions.…”
Section: Structural Insight Into the Spatialarrangement Of Prc2 Subunitsmentioning
confidence: 99%
“…PRC2 can bind to dinucleosomes through nucleosomal DNA interactions (Figure A). This interaction was visualized by a cryo‐EM structure reported by the group of Nogales . One of the pair of nucleosomes is an unmodified substrate, and the other one has histone H3K27me3 marks.…”
Section: Introductionmentioning
confidence: 99%